Post-modern Representation in Ceros and Batazor Novels Written by Tere Liye: Jeans Francois Lyotard Post-modernism - Alfadlilah, Muna (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2020)
Literature work is a notion which results a masterpiece with certain characteristics and it has aesthetics value. Understanding and enjoying literature work requires literature theoretical understanding. Literature theory explains to readers which will lead to a certain understanding or theory in a phenomenon consisted in it. This research aims to describe post-modern cultural aspects based on Jhon Francois Lyotard's theory in a novel written by Tere Liye, Ceros and Batazor edition. Tere Liye’s novel has data elaborating post-modernism aspects, such as electism, parody, pastiche, irony, and camp. The data source of this research is a novel written by Tere Liye, Ceros and Batazor edition. The data collection was done by reading and noting methods. This research was done by identifying, clarifying, analyzing, elaborating, and drawing in order to create conclusion within postmodern aspects in which represented social life as described in novel written by Tere Liye, Ceros and Batazor edition. The findings of Tere Liye’s novel describes fantasy and adventure words mixed in human lives and activities. They describe postmodern elements through several aspects. The research in Tere Liye’s novel, one of them is electism in which its behavior combines local and foreign cultures both from language or foreign good aspects. The parody element is uttered as criticism to describe or quip certain behaviors or activities done by society. Meanwhile, pastiche, in the novel is an event lasting as principles stated in the novel. Irony is a description of an unexpected occurred event or destiny. Camp in the novel is an emphasis on the characters’ behaviors which result to interpretation.